2019
DOI: 10.1101/2019.12.21.886051
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A dynamic normalization model of temporal attention

Abstract: Vision is dynamic, handling a continuously changing stream of input, yet most models of visual attention are static. Here, we develop a dynamic normalization model of visual temporal attention and constrain it with new psychophysical human data. We manipulated temporal attention-the prioritization of visual information at specific points in time-to a sequence of two stimuli separated by a variable time interval. Voluntary temporal attention improved perceptual sensitivity only over a specific interval range. T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 112 publications
(151 reference statements)
1
6
0
Order By: Relevance
“…The present study has larger implications. A common view is that selective perception is sufficient to account for all effects of partially valid cueing (e.g., Denison, Heeger, et al, 2017;Nobre & Ede, 2017). Based on our results, and the results we have cited in the literature, we argue that selective perception alone can be rejected.…”
Section: Relation To Previous Research On Temporal Cueingsupporting
confidence: 73%
See 2 more Smart Citations
“…The present study has larger implications. A common view is that selective perception is sufficient to account for all effects of partially valid cueing (e.g., Denison, Heeger, et al, 2017;Nobre & Ede, 2017). Based on our results, and the results we have cited in the literature, we argue that selective perception alone can be rejected.…”
Section: Relation To Previous Research On Temporal Cueingsupporting
confidence: 73%
“…In an early temporal cueing study, Coull and Nobre (1998;see also Griffin, Miniussi, & Nobre, 2001) used a character discrimination task, and their most relevant conditions had SOAs of 0.3 and 1.5 s. The magnitude of the cueing effects declined sharply with SOA. In another study, Denison, Carrasco, & Heeger (2019) measured temporal cueing using fine orientation discrimination among Gabor patches and a postcue. They found near-zero cueing effects for a SOA of 800 ms, and cueing effects of up to 0.5 d′ units for short SOAs.…”
Section: Relation To Previous Research On Temporal Cueingmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible complication in two-target tasks is that the precue gives temporal information pertaining to both an absolute time (e.g., 1,000 ms after the precue) and serial order (e.g., the first target in the sequence). Varying the temporal interval between the two targets has shown that the degree to which a temporal precue affects perceptual sensitivity depends on the precise interval and, therefore, is not merely determined by serial order (Denison, Carrasco, & Heeger, 2017b). The continued use and development of behavioral protocols that manipulate temporal attention while controlling for other factors will advance the expanding effort to understand how we attend dynamically across time.…”
Section: Discussionmentioning
confidence: 99%
“…As a mental construct, selective attention (e.g., concentration, focusing, activation, selection) can be distinguished from attention as synthesis (i.e., feature integration; Treisman and Gelade [ 4 ]), attention as effort (Kahneman [ 5 ]), attention as a processing mode (top-down, bottom-up; endogenous or exogenous; parallel, serial, or hybrid (Palmer [ 6 ]; Carrasco [ 7 ]), attention as an individual difference (being attentive or distractible; global or analytic; Murphy [ 8 ], attention as “ stimulus control ” (attending to a stimulus means being controlled by it; e.g., Dinsmoor [ 9 ]), attention as a philosophical construct (choice or free will; awareness or consciousness; James [ 1 ]), and attention as a naive explanation , as in, “I didn’t look carefully after I stopped paying attention”. Attention can also be studied as a neurological construct (a change in single cell responses or in gross recordings like the EEG, VEP, or BOLD response) and as exemplifying underlying neural processes such as gain control and normalization (Desimone and Duncan [ 10 ]; Denison, Carrasco, and Heeger [ 11 ]). All of these usages can be found to apply in studies of vision, visual perception, and visual memory.…”
Section: Introductionmentioning
confidence: 99%